Therapeutic effect of hUC-MSCs from different transplantation routes on acute liver failure in rats - Wang, Yonghong; Wu, Bei; Tao, Yachao; Wang, Menglan; Wu, Dongbo; Chen, Enqiang; Tang, Hong (Frontiers in Medicine, 2025)
ObjectiveAcute liver failure (ALF) is a rare yet serious clinical syndrome. Recent studies have indicated that stem cells can effectively treat this condition. However, the optimal route for stem cell transplantation in the treatment of ALF remains unclear. This study aims to investigate the most effective transplantation route for stem cell therapy in ALF.MethodsHuman umbilical cord mesenchymal stem cells (hUC-MSCs) expressing both luciferase and green fluorescent protein were generated using a lentiviral vector. The hUC-MSCs were transplanted via the tail vein, portal vein, and abdominal cavity. The survival and distribution of the transplanted hUC-MSCs in rats were assessed through in vivo imaging and immunofluorescence. Furthermore, the therapeutic effects of hUC-MSCs transplanted via different routes on ALF were compared.ResultsThe survival time of hUC-MSCs transplanted via the tail vein and portal vein was shorter compared to those transplanted intraperitoneally. The distribution of hUC-MSCs varied by transplantation route: those injected via the tail vein and portal vein were primarily found in the lungs and liver, respectively, while intraperitoneally transplanted hUC-MSCs predominantly localized in the abdominal cavity. In ALF rats, hUC-MSCs transplanted via the tail vein and portal vein improved survival rates, enhanced liver pathology, and reduced levels of inflammatory cytokines in liver tissue. In contrast, abdominal transplantation of hUC-MSCs showed no significant therapeutic effect.ConclusionhUC-MSCs transplanted via the tail vein and portal vein exhibited similar therapeutic effects on ALF; however, abdominal transplantation of hUC-MSCs showed no significant effect.